Penyesuaian Gaya Belajar dengan Prinsip aliran Humanisme Berbasis Media PhET Kelas 6 SDN Telang 1 - Rodhiah, Rizky; A'yun, Dya (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2024)
This article explains an approach to adapting learning styles based on humanistic principles using PhET simulation media. Humanism in education emphasizes the development of individual potential and emphasizes meaningful learning experiences. PhET Simulations, on the other hand, are online learning resources that provide interactive simulations for understanding scientific and mathematical concepts. The humanistic educational approach views students as unique individuals with different learning needs. Therefore, adapting learning styles is the key to achieving learning effectiveness. PhET Simulation Media allows students to learn through virtual experiments and conceptualize abstract ideas practically. This article examines various learning styles that can be identified through a humanistic approach, including visual, auditory, and kinesthetic learning styles. Each learning style has its preferences regarding understanding and retaining information. PhET simulation provides the right solution to accommodate these different learning styles by presenting learning material through visualization, audio, and kinesthetics. In this context, this article also presents research findings and case studies that show how the implementation of PhET simulations succeeded in improving the understanding of certain concepts for students with certain learning styles. The results of this research provide practical insights for educators to identify student learning styles and incorporate the use of PhET simulations into everyday learning. Educators can create learning environments that support students' holistic growth by integrating humanism, learning style adaptation, and interactive simulation technologies such as PhET. This article invites readers to consider the importance of incorporating humanistic principles into learning design to provide meaningful and relevant learning experiences for all students. Keywords: Learning Style, Humanism, Simulation Media